Informing the ethical review of human subjects research utilizing artificial intelligence - Makridis, Christos Andreas; Boese, Anthony; Fricks, Rafael; Workman, Don; Klote, Molly; Mueller, Joshua; Hildebrandt, Isabel J.; Kim, Michael; Alterovitz, Gil (Frontiers in Computer Science, 2023)
The rapid expansion of artificial intelligence (AI) has produced many opportunities, but also new risks that must be actively managed, particularly in the health care sector with clinical practice to avoid unintended health, economic, and social consequences. Given that research and development (R&D) involving human subjects is reviewed and rigorously monitored by institutional review boards (IRBs), we argue that supplemental questions added to the IRB process is an efficient risk mitigation technique available for immediate use. To facilitate this, we introduce AI supplemental questions that provide a feasible, low-disruption mechanism for IRBs to elicit information necessary to inform the review of AI proposals. We pilot the questions within the Department of Veterans Affairs – the nation’s largest integrated healthcare system – and demonstrate its efficacy in risk mitigation through providing vital information in a way accessible to non-AI subject matter experts responsible for reviewing IRB proposals. We provide these questions for other organizations to adapt to fit their needs and are further developing these questions into an AI IRB module with an extended application, review checklist, informed consent, and other informational materials.